EXPLORING BIOCHEMICAL PATHWAYS IN RHEUMATOID ARTHRITIS: INSIGHTS INTO ANTI-INFLAMMATORY ROLES OF TRACE ELEMENTS AND URSOLIC ACID - Farhana Ayub; Abdul Khaliq Naveed; Adnan Jehangir (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Rheumatoid arthritis (RA) is an autoimmune disease involving complex pathways driven by cytokine dysregulation and oxidative stress. This article investigates the role of trace elements such as copper (Cu), selenium (Se), and zinc (Zn) in the treatment of RA and their biochemical pathways about ursolic acid (UA). Experiments performed in a mouse model of arthritis show that UA when combined with metal complexes, improves therapeutic cytokine protection while inhibiting inflammatory cells such as NF-A, TLR-4, and TNF-alpha. Molecular interactions in this biochemical process have been shown to have two roles: inhibiting inflammation and promoting tissue repair. Additionally, UA complexes have negligible toxicity and have been suggested for use as alternative therapies or treatments such as nonsteroidal anti-inflammatory drugs. This information provides a way to use natural and therapeutic interventions to target the effects of RA and improve patient outcomes.